PENGARUH E-SUPERVISI TERHADAP DISIPLIN KERJA DAN KOMPETENSI GURU SMK TUNAS TIMUR ELOPADA, SUMBA BARAT DAYA, NUSA TENGGARA TIMUR - Nicson Alfa Tena Bolo; Nuril Huda; Hairussaleh (Tamilis Synex: Multidimensional Collaboration, 2024)
This research examines the influence of supervision, work discipline and competency on the performance of teachers at Tunas Timur Elopada Vocational School, Southwest Sumba, East Nusa Tenggara. The population in this study were all teachers at Tunas Timur Elopada Vocational School, Southwest Sumba, East Nusa Tenggara, totaling 32 people. The sampling technique in this research is saturated sampling (census), which is a sampling technique when all members of the population are used as samples. So the number of samples taken in this research was 32 respondents, namely teachers at SMK Tunas Timur Elopada, Southwest Sumba, East Nusa Tenggara. The analytical tool used is multiple linear regression with the help of SPSS 21.0 software. The results of the research show that supervision (X1), work discipline (X2), and competence (X3) have a simultaneous and partial effect on the performance of Teachers (Y) of SMK Tunas Timur Elopada, Southwest Sumba, East Nusa Tenggara, and competence (X3) has an effect dominant on the performance of Teachers (Y) of SMK Tunas Timur Elopada, Southwest Sumba, East Nusa Tenggara